NACA 0020 Horizontal Axis Wind Turbine Design Optimization to Increase Coefficient of Power (Cp) - Suyono, Tri; Umron, Amat; Harbelubun, Mohammad Muzni (Universitas Khairun, 2025)
Renewable energy is the primary solution to future energy challenges. Horizontal-axis wind turbines (HAWTs) have great potential as a source of clean energy, especially in remote areas. This study aims to optimize the number of HAWT blades to increase the Coefficient of Power (Cp) through simulation and experimental methods. Optimization is done by modifying the angle of attack and the number of blades. Aerodynamic simulations using the QBLADE software were validated through laboratory experiments with small-scale prototypes. The study calculated the harvestable wind energy using the Betz limit (59%) and the Cp range from the previous study (35-45%). The turbine's efficiency is strongly influenced by the number of blades operating based on lift, with the glide ratio being an important parameter. The turbine blade was manufactured using NACA 0020 at the Mechanical Engineering workshop at Khairun University. Testing is carried out in the laboratory to measure the relationship between the number of blades, rotor rotation, and the generator's output power. This process accounts for mechanical, generator, and heat losses. The experimental data is validated by simulation and calculation to formulate the number of blade relationships as design recommendations. Based on analyses of the relationships among Cp, Cm, and TSR, and comparisons with previous studies, the number of wind turbine blades was shown to have a significant effect on aerodynamic efficiency, initial torque, and energy conversion performance. The 2-blade turbine is well-suited to strong winds due to its high efficiency at high TSRs, but it is less stable and has low starting torque. The 6-blade turbine excels at low TSR with ample initial torque, ideal for slow winds and mechanical applications, although its efficiency decreases at high TSR. 3-blade turbines offer the best compromise, making them a top choice in commercial systems.